Epithet and Esteem: The Reception of Momus in Early Modern English Culture. - Navitsky, Joseph (International Journal of the Classical Tradition, 2020)
The article presents the scene in Ben Jonson's Poetaster, a play set in ‘Augustus Caesar's times. Topics include showing the appropriate role of the writer in early modern English society where the character Ovid hosting a feast to the visitors; capturing the divergent attitudes harbouring by early modern English culture towards the little-known Greek deity Momus; and establishing the full range of responses to the mysterious figure from antiquity.